HEAT ON Khalid: 'Pas can't save Khalid's job'. Contentious: Party's support insufficient to neutralise efforts by PKR to oust him, say analysts - Ariff, Syed Umar (New Straits Times, 2014)
TAN Sri Abdul Khalid Ibrahim's position as Selangor menteri besar is safe for now, but it remains uncertain how long it will last. The support he received from Pas was not enough to neutralise efforts and overtures by several PKR members to oust him from office, said political analysts.